Simultaneous listeria monocytogenes septicaemia in mother and pre-term infant. Issue 649 (November 1979) - Burgess, P.; Smith, C. S.; Ben-Musa, A.; Harris, F.
Abstract : Although infection by Listeria monocytogenes during pregnancy with subsequent infection of the fetus is well known, it is uncommon to encounter acute maternal septicaemia with the onset of premature labour and delivery of an infected infant. Such a case is described of maternal septicaemia with an infected liveborn preterm infant who was successfully treated and recovered.